Arterial Blood Gas Analysis and the Outcome of Treatment in Tricyclic Antidepressants Poisoned Patients with Benzodiazepine Coingestion - Ahmad Yaraghi; Nastaran Eizadi-Mood; Maryam Katani; Shadi Farsaei; Mahrang Hedaiaty; Seyyed Mohammad Mahdy Mirhosseini; Elham Beheshtian; Ali Mohammad Sabzghabaee (Anesthesiology Research and Practice)
Background. Poisoning with tricyclic antidepressants (TCAs) is still a major concern for emergency physicians and intensivists. Concomitant ingestion of other psychoactive drugs especially benzodiazepines with TCAs may make this clinical situation more complex. This study aimed to compare the arterial blood gas (ABG) values and the outcome of treatment in patients with coingestion of TCA and benzodiazepine (TCA + BZD) poisoning and TCA poisoning alone. Methods. In this cross-sectional study which was carried out in a tertiary care university hospital in Iran, clinical and paraclinical characteristics of one hundred forty TCA only or TCA + BZD poisoned patients (aged 18–40 years) were evaluated. ABG analysis was done on admission in both groups. Outcomes were considered as survival with or without complication (e.g., intubation) and the frequency of TCA poisoning complications. Results. Arterial pH was significantly lower in TCA + BZD poisoning group compared with TCA only poisoning group (7.34 ± 0.08 and 7.38 ± 0.08, resp.; P=0.02). However, other complications such as seizure, and the need for the endotracheal intubation were not significantly different. All patients in both groups survived. Conclusions. Concomitant TCA plus BZD poisoning may make the poisoned patients prone to a lower arterial pH level on hospital admission which may potentially increases the risk of cardiovascular complications in TCA poisoning.